2017
DOI: 10.1002/pat.4075
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and characterization of electrospun chitosan/poly(vinyl alcohol) nanofibers as a phenol adsorbent via response surface methodology

Abstract: Fabrication and characterization of chitosan/poly(vinyl alcohol) electrospun nanofibers for adsorption of phenol from water were investigated. The effects of voltage (15–30 kV), solution injection flow rate (0.5–1.5 ml/hr), distance of needle and collector (10–20 cm) and chitosan/poly(vinyl alcohol) ratio (25/75, 50/50, 75/25) were studied to obtain the optimum electrospinning conditions for the maximum adsorption capacity of phenol. Central composite design (CCD) was used to investigate and optimize the proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…As a result, increased surface charge density results in nanofibers with smaller diameters and increases the drag force imposed on the polymer jet flow. 45,46
Figure 5.Main effects of the defined variables on CS/PEO fiber diameter a) concentration, b) voltage, c) distance, and d) angle.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, increased surface charge density results in nanofibers with smaller diameters and increases the drag force imposed on the polymer jet flow. 45,46
Figure 5.Main effects of the defined variables on CS/PEO fiber diameter a) concentration, b) voltage, c) distance, and d) angle.
…”
Section: Resultsmentioning
confidence: 99%
“…result, increased surface charge density results in nanofibers with smaller diameters and increases the drag force imposed on the polymer jet flow. 45,46 The obtained term coefficient between electrospinning parameters and response variables indicated that the mean diameter of nanofibers significantly decreased with an increase in the applied voltage (r = À 0.267, p value <.0001). In Figure 5(b), The inverse relationship between the applied voltage and the average diameter of the fiber is explained by the fact that increasing the applied voltage increases the strength of the electric field and electrostatic stretching force, which results in an accelerated jet and thinner nanofibers.…”
Section: Investigation Of the Effect Of Processing Variables On The R...mentioning
confidence: 96%
“…In electrospinning process, the entrapment of cells in nanofibers can be achieved by direct electrospinning of cells with other components such as polymers. Commonly, water soluble polymers are used to entrap cells due to their properties such as good fiber forming characteristic, non-toxic, able to retain high bioavailability of the cells and will undergo solvent evaporation during the electrospinning process which can help in extending the shelf life of cells [39,40].On top of that, these polymers show relatively high degradation in aqueous environment which is desirable in applications that need quick release of cells [21]. Therefore, in most cases, water soluble polymers have been used to dissolve the cells so that they can form homogenous solution with the cells.…”
Section: Entrapment Principle Of Cells In Electrospun Nanofibersmentioning
confidence: 99%
“…Linear or square polynomial functions are employed to describe the system studied and to explore (modeling and displacing) the optimal experimental conditions. [7] Regression analysis is a modeling technique, which determines the relationship between a dependent (target) and independent variables (predictor). Using the regression methods, the experimental data thus obtained were utilized to build mathematical models which analyze the optimal conditions for the process.…”
Section: R Ecombinantmentioning
confidence: 99%